1999
DOI: 10.1021/ja9915347
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the urdGT2 Gene, Which Encodes a Glycosyltransferase Responsible for the C-Glycosyltransfer of Activated d-Olivose, Leads to Formation of the Novel Urdamycins I, J, and K

Abstract: A targeted search for glycosyltransferase (GT) encoding genes in the gene cluster of the urdamycin A producer Streptomyces fradiae Tu ¨2717 resulted in the discovery of urdGT2, a GT encoding gene located approximately 7 kb downstream of the minimal polyketide synthase (PKS) encoding genes. Subsequent inactivation of this gene created a mutant strain, which produces completely different metabolites than the wild-type strain, consisting of the three new urdamycins I, J, and K. Their structures provide new insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 27 publications
1
58
0
8
Order By: Relevance
“…Only a few C-GTs involved in the biosynthesis of natural products have been characterized so far, such as, the pathogen-associated C-GT IroB [31] or UrdGT2. [16][17][18] C-Glycosylated products are of particular interest as they are stable against glycosidase degradation. [32] We resequenced the putative gilGT gene which was believed to encode the C-GT involved in the biosynthesis of GV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few C-GTs involved in the biosynthesis of natural products have been characterized so far, such as, the pathogen-associated C-GT IroB [31] or UrdGT2. [16][17][18] C-Glycosylated products are of particular interest as they are stable against glycosidase degradation. [32] We resequenced the putative gilGT gene which was believed to encode the C-GT involved in the biosynthesis of GV.…”
Section: Discussionmentioning
confidence: 99%
“…The highest homologies were found with LanGT2 (38% amino-acid identity), a GT presumed to be involved in attaching the first D-olivose to landomycin aglycon, [13][14][15] and UrdGT2 (31% amino-acid identity), which is the C-GT of the urdamycin biosynthetic pathway. [16][17][18] The previously reported putative GilGT protein had 495 amino acids, which is approximately 120 amino acids longer than any other polyketide GT found so far. [11] Because several attempts to generate a gilGT mutant by in-frame deletion failed (data not shown), we resequenced the entire region of the gene cluster and found a sequencing error (see Supporting Information).…”
Section: Sequence Analysismentioning
confidence: 99%
“…[1][2][3][4][5][6] The landomycins are closely related to the urdamycins (e.g., urdamycin A (5)). [7][8][9] Both possess a polyketide-derived angucyclinone core and sugar moieties consisting of D-olivose and L-rhodinose building blocks. Major structural differences were found in the assembly of the sugar moieties and in the oxygenation pattern of the polyketide core moiety.…”
mentioning
confidence: 99%
“…In landomycin biosynthesis, all but one oxygenation step in the aglycon formation appear to occur prior to the first GT step, [5] while for the urdamycin biosynthesis the sequence of biosynthetic events (oxygen attachment at 12-and 12b-positions by UrdE and UrdM, respectively, before or after the C-glycosylation step) remained the subject of debate, and the nature of the acceptor substrate of the important C-glycosyltransferase UrdGT2 was still ambiguous. [8,11] Here we describe our attempts to further investigate UrdGT2, to identify its acceptor substrate, and to possibly generate C-glycosidic landomycin derivatives through heterologous expression of the corresponding gene urdGT2. Our work has showed that the C-glycosylation in the urdamycin biosynthesis occurs prior to the two aglycon oxygenations through oxygenases UrdE and UrdM, and that the early intermediate UWM6 serves as the acceptor substrate for UrdGT2.…”
mentioning
confidence: 99%
See 1 more Smart Citation